After the empire the breakdown of the American order - Todd, Emmanuel 1951- (Columbia Univ. Press, 2003)
A historian and anthropologist use demographic and economic factors to explain the waning hegemony of the United States.
Keywords: Buitenlandse politiek; Geopolitiek; Géopolitique - États-Unis; Internationale orde; Außenpolitik; Geopolitics -- United States; Weltordnung; Verlust; Großmacht; Scheitern; Weltpolitik; Hegemonie; Internationaler Terrorismus; États-Unis - Relations extérieures - 2001-; USA; United States -- Foreign relations -- 2001-